2022
DOI: 10.3390/ijerph192215092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ambient Illuminance on Explicit and Implicit Altruism: The Mediation Roles of Perceived Anonymity and Satisfaction with Light

Abstract: Ambient light plays a key role in social interactions, and the effects of ambient light on explicit altruism have been widely documented. However, whether ambient light affects implicit altruism and the potential mechanisms underlying the effect remain largely unknown. The current study aimed to explore the effects of ambient illuminance on explicit and implicit altruism simultaneously, and to determine the potential mediation role of subjective mood, state self-control perceived anonymity and satisfaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(109 reference statements)
0
1
1
Order By: Relevance
“…Moreover, the influence of brightness on pro-social behavior is believed to be mediated, in part, by satisfaction with illumination and perceived anonymity [26]. Intriguingly, the findings on perceived anonymity by Ru et al (2022) differ from those of the present study. They observed that variations in brightness affected participants' perceived anonymity.…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the influence of brightness on pro-social behavior is believed to be mediated, in part, by satisfaction with illumination and perceived anonymity [26]. Intriguingly, the findings on perceived anonymity by Ru et al (2022) differ from those of the present study. They observed that variations in brightness affected participants' perceived anonymity.…”
Section: Plos Onecontrasting
confidence: 99%
“…It has been reported that the effect of brightness on pro-social actions may be moderated by societal factors, such as self-construal [ 25 ]. Moreover, the influence of brightness on pro-social behavior is believed to be mediated, in part, by satisfaction with illumination and perceived anonymity [ 26 ]. Intriguingly, the findings on perceived anonymity by Ru et al (2022) differ from those of the present study.…”
Section: Discussionmentioning
confidence: 99%